The Effect of Bank Sulselbar's People's Business Credit (KUR) on MSME Development in Masamba District - Tinanti S; I Ketut Patra; J. Jusman (Golden Ratio of Mapping Idea and Literature Format, 2026)
Limited access to formal financing remains a major constraint on the development of micro, small, and medium enterprises (MSMEs), particularly in regional areas. Through the People's Business Credit (KUR) program, the government seeks to address this constraint by providing accessible, low-interest financing. However, the effectiveness of KUR in promoting MSME development at the local level still requires empirical verification. Therefore, this study explicitly addresses the following research question: Does the People's Business Credit (KUR) distributed by Bank Sulselbar have a significant effect on MSME development in Masamba District? Based on this question, the research hypothesis states that KUR has a positive and significant effect on MSME development. This study employed a quantitative approach using a survey of MSME owners who had received KUR in Masamba District. The data were analyzed using simple linear regression to examine the relationship between People's Business Credit and MSME development, as measured by revenue growth, increased assets, and employment creation. By formulating a clear research question and hypothesis, this study is expected to provide a strong empirical basis for assessing the role of KUR as an inclusive financing instrument for MSME development at the local level.